Measurement of W gamma and Z gamma production in proton-proton collisions at root s=7 TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (2011)
A study of W ±Z production in proton-proton collisions at √s = 7 TeV is presented using data corresponding to an integrated luminosity of 4. 6 fb -1 collected with the ATLAS detector at the Large Hadron Collider in 2011. In total, 317 candidates, with a background expectation of 68±10 events, are observed in double-leptonic decay final states with electrons, muons and missing transverse momentum. The total cross-section is determined to be σ WZ tot = 19. 0 -1.3 +1.4(stat.)±0.9(syst.)±0.4(lumi.) consistent with the Standard Model expectation of 17.6 -1.0 +1.1. Limits on anomalous triple gauge boson couplings are derived using the transverse momentum spectrum of Z bosons in the selected events. The cross-section is also presented as a function of Z boson transverse momentum and diboson invariant mass. © 2012 CERN for the benefit of the ATLAS collaboration.